2014
DOI: 10.22230/src.2014v5n3a161
|View full text |Cite
|
Sign up to set email alerts
|

From Research to Action: Four Theories and Their Implications for Knowledge Mobilization

Abstract: Integral to both knowledge mobilization and action research is the idea that research can and should ignite change or action. Change or action may occur at multiple levels and scales, in direct and predictable ways and in indirect and highly unpredictable ways. To better understand the relationship between research and action or change, we delineate four conceptualizations that appear in the literature. Reflecting on our experiences as collaborators in a community–university action research proj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…The source of change is located not in the instrumental deployment of research findings but in the participants themselves. (Mosher et al, 2014, p. 7).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The source of change is located not in the instrumental deployment of research findings but in the participants themselves. (Mosher et al, 2014, p. 7).…”
Section: Discussionmentioning
confidence: 98%
“…In this section I explored the first research question posed; that is: What kinds of knowledge brokering work, what processes and products are there in the international education research‐practice space and how have they been characterised? I found that: it was difficult to distinguish between policy and practice in educational knowledge brokering there are a variety of terms used in the research‐into‐use space in education in confusing and non‐distinct ways, which is holding the field back; I proposed reconciling knowledge mobilisation and knowledge brokering, but preferred knowledge brokering knowledge brokering in education is not well defined, but is often regarded as a process of transforming knowledge from research into practice by crossing or spanning boundaries various models and metaphors have been proposed, such as knowledge brokering as mediating, straddling, Janusian integration, boundary blurring, boundary spanning, translation and matchmaking, all with various connotations about the type of work involved several frameworks have been proposed to characterise, describe, prescribe, evaluate or measure knowledge brokering, but they often lack detail, clear aims, or a wide perspective of the field; I suggested Mosher et al (2014) as the most useful for analysis at the level that this paper seeks to take. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ACT for Youth committed, at inception, to extensively recruit, hire, and train youth from the Jane-Finch community as peer interviewers and involve them in knowledge mobilization and communication activities and build their capacity to take leadership roles in addressing important issues in their communities and lives. As a project that sought to enhance youth and community well-being and promote youth-driven social change, ACT for Youth was a significant opportunity for CER as a form of social work, despite tensions and unique dynamics as a community-university research partnership that was based in a university with an overarching hierarchical structure of knowledge production (Mosher et al 2014;Nichols et al 2013).…”
Section: Challenges Of Youth Engaging Community-engaged Researchmentioning
confidence: 99%
“…Relatedly, with a growing appreciation for the importance of youth participation and voice in the decisions that impact their day-to-day lives (Arunkumar et al 2018;Jardine and James 2012), interest about the benefits that engaged research offers to youth and communities has also increased (Hawke et al 2018). With global shifts in youth policies, practices, and research toward positive youth development (PYD), a strengths-based and asset-building approach for youth development (Lerner et al 2005), there is great potential of CER to shift the idea of youth as just consumers and objects of knowledge to youth as producers of knowledge (Mosher et al 2014;Nichols et al 2013). Importantly, CER projects informed by PYD has the potential to support youth well-being by providing opportunities for youth, including to those who face marginalization, to develop skills, leadership, civic engagement, and empowerment (Ardoin et al 2014;Flicker 2008;Ozer 2017;Ozer et al 2010;Ozer and Wright 2012;Powers and Tiffany 2006;Tintiangco-Cubales et al 2016).…”
Section: Introductionmentioning
confidence: 99%